Pengaruh Terapi Bermain Mendongeng dengan Penurunan Tingkat Kecemasan pada Anak Usia Pra Sekolah Akibat Hospitalisasi - Pawiliyah Pawiliyah; Liza Marlenis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the effect of storytelling play therapy with a decrease in anxiety levels in pre-school age children due to hospitalization in Dr. Sobirin Lubuklinggau. The study design used a pre-experimental one group pre-post test design. The results obtained mean a decrease in anxiety 10.50, with the results of the Wilcoxon Test Asym 0,000 <0.005. The conclusion of this study is the effect of storytelling play therapy on pre-school age anxiety scores of children treated at RSUD Dr. Sobirin Lubuklinggau. Keywords: Anxiety, Storytelling, Child Care, Play Therapy